Trauma Coping Self-Efficacy Mediates Associations Between Adult Attachment and Posttraumatic Stress Symptoms - Morison, Margaret; Benight, Charles C. (Frontiers in Psychology, 2022)
Attachment orientations reflect individuals’ expectations for interpersonal relationships and influence emotion regulation strategies and coping. Previous research has documented that anxious and avoidant attachment orientations have deleterious effects on the trauma recovery process leaving these survivors vulnerable to posttraumatic stress disorder (PTSD) symptoms. However, avoidant attachment may be more complicated. Prior work has also found those high in avoidant attachment but also low in anxious attachment (i.e., dismissing) may not experience such vulnerabilities. Further, avoidant attachment individuals often report higher self-efficacy than their anxiously attached counterparts. The present study examined trauma coping self-efficacy as a previously unexamined mechanism of action between adult attachment and PTSD symptoms. Structural equation modeling results showed that anxious attachment was associated with lower CSE-T and greater PTSD symptoms six weeks later. Further, a significant indirect effect of anxious attachment on PTSD symptoms through CSE-T was found. Contrary to hypotheses, avoidant attachment also exhibited an indirect effect on PTSD symptoms through CSE-T, such that avoidant attachment was associated with lower CSE-T, which in turn, was associated with greater PTSD symptoms. Also contrary to hypotheses, the interaction between anxious and avoidant attachment was not significantly associated with either CSE-T or PTSD symptoms. Results suggest that both anxious and avoidant attachment orientations contribute to poor self-regulation following trauma, as they undermine perceptions of trauma coping self-efficacy.